2022
DOI: 10.1177/21514593221124414
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Administration at Hospital Admission Decreases Transfusion Rates in Geriatric Hip Fracture Patients Undergoing Surgery

Abstract: Introduction The timing of tranexamic acid (TXA) administration in fragility hip fracture patients is controversial. Prior studies have demonstrated reduction in transfusion requirements using the two-dose arthroplasty model. However, unlike arthroplasty patients whose bleeding starts at the time of surgical incision, hip fractures have an onset of bleeding at the time of the injury. The primary goal of this study was to evaluate the optimal timing of TXA administration and to determine its effect on red blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, there has been an increase in literature regarding the early administration of TXA upon admission. Moran et al found in their prospective analysis a statistical benefit in the early administration of TXA in hip fractures [17]. Another prospective randomized controlled trial showed similar findings in the administration of TXA upon admission; a statistically significant improvement in hemoglobin drops, and transfusion rates [18].…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, there has been an increase in literature regarding the early administration of TXA upon admission. Moran et al found in their prospective analysis a statistical benefit in the early administration of TXA in hip fractures [17]. Another prospective randomized controlled trial showed similar findings in the administration of TXA upon admission; a statistically significant improvement in hemoglobin drops, and transfusion rates [18].…”
Section: Discussionmentioning
confidence: 80%
“…Nikolaou et al demonstrated that a single preoperative dose of 15 mg/kg TXA benefits older patients undergoing IMN treatment for these fractures [ 35 ]. Other studies have reported the effectiveness of different TXA administration strategies in reducing postoperative bleeding for elderly hip fracture patients [ 36 ]. For example, Zhang et al reported that administering 1 g of intravenous TXA 10 min before incision and 3 h after significantly reduces HBL and the need for allogeneic red blood cell transfusion, without increasing thrombotic events, including DVT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%